The Impact of Principals' Human Resource Management Competencies on Elementary School Teachers' Performance in Majalengka Regency - Bajuri, Diding; Nahdi, Dede Salim; Cahyaningsih, Ujiati (Papanda Publisher, 2025)
This study explores the impact of principals’ human resource management (HRM) competencies on elementary school teachers’ performance in Majalengka Regency, Indonesia. Given the strategic role of school principals in managing educational resources, especially teachers, this study aims to examine how specific dimensions of HRM competencies contribute to teacher performance. A quantitative, correlational research design with a cross-sectional survey approach was used. The study involved 400 teachers from 80 public elementary schools selected through proportionate stratified random sampling. Data were collected using validated questionnaires measuring HRM competencies (six dimensions) and teacher performance (four dimensions). Statistical analyses included descriptive statistics, Pearson correlations, simple and multiple linear regressions, and Structural Equation Modeling (SEM). The findings revealed that principals’ HRM competencies significantly influenced teacher performance (R² = 0.615, p < 0.001). Among the HRM dimensions, human resource development had the strongest effect (β = 0.402), followed by performance appraisal (β = 0.234) and HR planning (β = 0.203). Teacher performance was generally high, particularly in personality and pedagogical competencies. All regression assumptions were met, confirming the robustness of the analysis.The results suggest that effective HRM by school principals, especially in continuous professional development and fair performance evaluations, plays a pivotal role in enhancing teacher performance. However, compensation and work relationship dimensions showed room for improvement, indicating potential policy gaps. Principals’ HRM competencies are vital for improving teacher performance. Educational policymakers should prioritize leadership development programs focusing on HRM strategies to strengthen teacher quality and educational outcomes at the elementary level.